MENGUKUR KINERJA LAYANAN RUMAH SAKIT BHAYANGKARA PALANGKA RAYA DITINJAU DARI PERSPEKTIF PELANGGAN - Ivan Marenda; Usup Riassy Christa; Luluk Tri Harinie (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
This research aims to analyze, test, and measure the performance of BhayangkaraHospital Palangka Raya Services in terms of Customer Perspective. The type of thisresearch is quantitative descriptive. The data collected are secondary data and primarydata. The secondary data was obtained from the documentation of medical recordreports of the year 2020-2022. The primary data was obtained through questionnairesdistributed to patients of Bhayangkara Hospital Palangka Raya. The results showed thatthe hospital's performance from the customer perspective calculated based oncustomer retention and customer acquisition in 2020-2022 was on average good.Meanwhile the customer satisfaction indicators from five variables, namely tangibles,reliability, responsiveness, assurance and empathy, were generally classifiedassatisfactory. The management needs to pay special attention to the assessment ofindicators that have not been good or good enough, and maintain the assessment ofgood indicators in order to improve the hospital’s performance in the future.